A proibição de distribuição de sacolas plásticas descartáveis: uma análise a partir da proteção ambiental e da liberdade econômica - Brioschi, Lívia (2023)
Plastic is one of the most widely used materials due to their versatility, as they are cheap, water resistant, durable and at the same time malleable enough to be used in different industries. Poor waste management and widespread consumption of disposable plastic items, known for their short service life, such as cutlery, straws, and bags, makes Brazil one of the largest producers of this type of waste. Therefore, it is possible to find small plastic particles, called microplastics, anywhere in nature including in the human body. Due to the lack of Brazilian legislation at the federal level to combat plastic pollution, there is a growing trend of state and municipal legislation that restrict or prohibit the consumption of these disposable objects, especially plastic bags. However, associations and representatives of the plastic industry frequently question the constitutionality of these laws in the Judiciary, claiming the violation of free initiative as a prerogative of economic freedom guaranteed by the Federal Constitution of 1988. The debate reached the Federal Supreme Court in different processes, and it recognized the general repercussion of the theme in Extraordinary Appeal n. 732686. Given this context, this research seeks to assess whether prohibitions on the delivery of plastic bags in commercial establishments are materially constitutional. From the deductive method, through a bibliographical and documentary research, the study focused on analyzing the constitutional principle of economic freedom and the fundamental rights and duties related to the environment. It is concluded that these provisions are constitutional, since the Constitution itself adopts the theory of sustainable development that imposes a necessary confluence between environmental protection and economic freedom.